Impact of antisperm antibodies on sperm functions and fertility in livestock: A narrative review - Channareddi Kuntareddi; Kamaraj Elango; Pradeep Nag; Arumugam Kumaresan (Asian Pacific Journal of Reproduction)
Spermatozoa are recognized as foreign cells by both male and female immune systems, leading to the production of antisperm antibodies (ASAs) when sperm are exposed to immune system due to a breach in the mucosal barrier. ASAs can be found in both sexes, though concentrations vary by individual and sex. This review examines ASAs production, their specific binding locations on sperm, and how ASAs may impair key sperm functions, including motility, viability, acrosome reaction, and capacitation. While ASAs are known to potentially interfere with sperm quality and sperm binding to zona pellucida in both humans and livestock, their impact on fertility remains debated, as ASAs are also detected in a significant number of fertile individuals. Furthermore, the practical relevance of ASAs screening in fertility assessment lacks consensus, with some findings suggesting that ASAs might even aid fertilization under certain conditions. By compiling the information on ASAs and their effects on semen quality and fertility, this review aims to provide a comprehensive understanding of the role of ASAs in infertility.